Balancing degradability and mechanical strength in keto modified polyethylene through hydrogen bonds - Li, Ke (2024)
Enhancing the degradability of polyethylene (PE) through keto group incorporation stands as a rising research frontier. The overall impact of these functional groups on PE’s degradability and mechanical properties at the atomic scale is not fully understood. Employing computer simulations, we investigate the degradability and mechanical properties of keto-modified PE (KMPE). Adding keto groups to the PE chain decreases its photostability, our findings reveal that increase in keto group concentration further amplifies degradation, albeit with minimal impact on photostability. Increasing the keto content (up to 5% in our simulations) leads to reduced polymer crystallinity, while the associated loss in mechanical strength is limited. This study shows that hydrogen bonding plays a compensatory role in KMPE by mitigating the reduction in mechanical properties due to keto group addition, effectively counterbalancing structural alterations to maintain mechanical integrity. These insights deepen our understanding of KMPE’s structure-property relationship, guiding the design of degradable materials.